Risk and Return of the KLSE Finance Stocks and the Performance of Banking Stocks in Malaysia - Mohd Ripin, Zarazila (1997)
The purpose of this study is to investigate the relationship between risk and return of fifty Finance Stocks listed on the Main Board of Kuala lumpur Stock Exchange for the period of 30th May 1995 to 30th May 1997. In addition to this objective, the performance of Big Five local Banks in relations to the KlSE FinanCe Index is also analyzed using the Performance Measurement Indices of Sharpe, Treynor and Jensen. The study found that during the above period, the Maybank stock is the least riskiest finance stocks in the top Five local Banks. For other finance stocks, Phileo Allied Berhad is the riskiest security while Bank Islam Malaysia Berhad is least riskiest. The return for Finance Stocks is 60% more than the return on the Composite Index as reflected by the Beta Coefficient. Finance Stocks have high positive correlations relative to the Composite Index. The study has also corraborates the hypothesis that the return of securities with high betas to be greater than the returns of the securities with low betas, consistent with risk-return theoretical relationship.